Chemical signatures of planets in the spectrum of solar twins - Martos, Giulia (2025)
Precise chemical abundances are key for the characterization of planet hosts, since the formation and the presence of planets around the stars can alter their chemical composition, creating fingerprints that are revealed through a detailed analysis of the spectrum. In this work, a Machine Learning algorithm was developed to obtain the atmospheric parameters and chemical abundances of 20 elements for a sample of 99 solar twins automatically from their high quality spectra obtained with the HARPS spectrograph, installed at the 3.6 meters telescope at the La Silla Observatory from ESO. The results obtained are in line with the literature, with average differences and standard deviations of (2 ± 27) K for Teff , (0.00 ± 0.06) dex for log g, (0.00 ± 0.02) dex for [Fe/H], (0.01 ± 0.05) km/s for micro turbulence velocity, (0.02 ± 0.08) km/s for macro turbulence velocity and (0.12 ± 0.26) km/s for projected rotational velocity. Regarding the chemical abundances, we reached a precision of 0.01 dex for the elements Na, Mg, Al, Si, Ca, Ti, Cr, Co, Ni e Cu, and most of the other elements agree within 0.01 and 0.02 dex with the literature. The abundances were corrected from the effects of the Galactic Chemical Evolution through a fitting versus the age of the stars and analyzed with the condensation temperature to verify if the stars presented depletion of refractories compared to volatiles. It was found that the Sun is more depleted in refractories than 89% of the twins, with a significance of 9.5 sigma when compared to the stars without planets and 4.3 sigma when compared to the stars with planets. We also identified a possible presence of three stellar subpopulations: one Cu-rich, one Cu-poor and the other is slightly older (age > 6 Gyr) and Na-poor. Possible origins of these groups are the migration of the stars from the central parts of the galactic disk and the initial chemical composition of their birth place.